The factors of children obsession towards gadgets / Amrina Shamsuddin ... [et al.] - Shamsuddin, Amrina; Ahmad Zamani, Naili; Ramlan, Nur Farah Farhana; Mohd Azhar, Nur Farah Izzaty
The appearance of technology has brought many positive as well as negative impacts. The research will be focusing more on the latter. The negative impact mentioned refers to the obsession of gadgets especially among young children. The obsession of gadgets among children is becoming more and more severe as generations pass and it is in the society·s best interest to curb such dire effects from further spreading. Obsession can lead to many problems and among them can range from a child's apparent l ack of social skills to the neglect of the child's own wellbeing. Through specific information gathering methods, the researchers have gathered data on the severity of the obsession, the experience of those involved as well as suggested possible solutions for the purpose of reducing the effects of gadget obsession amongst young children. It is hoped that through this research, this issue can and will be taken more seriously.